Использование лазеров для обработки и дезинфекции системы корневых каналов (Эндодонтия Today)
In modern dentistry it was convincingly shown that the laser radiation has the potential to destroy microorganisms. This article presents a literature review on the use of various laser systems for treatment and disinfection of root canals.